Pengaruh Live Streaming, Brand Image Dan Online Customer Review Terhadap Keputusan Pembelian Produk Maspion Di E-commerce Shopee Di Surabaya - Abdul Hadi; Andri Yanto (CV. ULIL ALBAB CORP, 2024)
Live streaming, Brand image, Online customer review are variables that have a big influence on purchasing decisions. Therefore, the researcher conducted a test using the multiple linear regression analysis method to obtain data information on how much influence. This research was conducted to determine the magnitude of the influence on purchasing decisions simultaneously and partially. These variables are live streaming, brand image, online customer riview and purchasing decisions can be measured using a ratio with a sample size of 100 consumers who buy maspion products. The data for each variable will be processed by means of a classic assumption test, namely normality, autocorrelation, multicollinearity and heteroscedasticity tests so that there is no bias and can be used in good regression analysis. Furthermore, researchers want to assess how much influence both simultaneously and partially is processed using multiple linear regression analysis using a computer application, namely the SPSS 23.0 application. After the researcher tests the data that has been collected, the results of the test are that the live streaming variable and brand image have a positive and significant effect, while the online customer review variable has a negative and insignificant effect on the purchasing decision variable.